DNA origami nanocalipers for pH sensing at the nanoscale. Issue 22 (28th February 2022) - Zhang, Xinyue; Pan, Li; Guo, Ruiyan; Zhang, Yueyue; Li, Fan; Li, Min; Li, Jiang; Shi, Jiye; Qu, Fengli; Zuo, Xiaolei; Mao, Xiuhai
Abstract : We report a shape-resolved nanomechanical device based on a DNA origami nanocaliper for pH sensing at the nanoscale. Abstract : A DNA origami nanocaliper is employed as a shape-resolved nanomechanical device, with pH-responsive triplex DNA integrated into the two arms. The shape transition of the nanocaliper results in a subtle difference depending on the local pH that is visible via TEM imaging, demonstrating the potential of these nanocalipers to act as a universal platform for pH sensing at the nanoscale.